1990
DOI: 10.1507/endocrj1954.37.685
|View full text |Cite
|
Sign up to set email alerts
|

Endocrinological Studies on TAP-144-SR, a Sustained-Release Formulation of a Potent GnRH Agonist (D-Leu6-(des-Gly10-NH2)-GnRH Ethylamide), in male Rats.

Abstract: The paradoxical effects of TAP-144-SR, a biodegradable sustained-release formulation of a potent GnRH agonist (TAP-144, leuprolide acetate) were evaluated in male rats by comparing its potency with that of TAP-144 solution.A single sc injection of TAP-144-SR (equivalent to 0.1 mg/kg/day as TAP-144), prepared by encapsulating the agonist in microcapsules of copoly (DLlactic/glycolic acid), suppressed serum levels of androgens, and the levels remained suppressed for 4 weeks.The potency of the paradoxical effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1991
1991
2004
2004

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…However, an earlier study using GnRHa revealed that desensitization of the pituitary actually occurred because pituitary concentrations of LH and FSH were suppressed and additional treatment with GnRHa did not stimulate gonadotropin release from the already stimulated pituitary (Sudo et al 1990). Curious effects of GnRHa on the PMSG-hCGinduced luteinization process of superovulated rats have been reported (Harwood et al 1980b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, an earlier study using GnRHa revealed that desensitization of the pituitary actually occurred because pituitary concentrations of LH and FSH were suppressed and additional treatment with GnRHa did not stimulate gonadotropin release from the already stimulated pituitary (Sudo et al 1990). Curious effects of GnRHa on the PMSG-hCGinduced luteinization process of superovulated rats have been reported (Harwood et al 1980b).…”
Section: Discussionmentioning
confidence: 99%
“…The treatment seemed not to cause desensitization of the pituitary gland, although changes in bioactive LH concentrations were not determined. However, a study using GnRHa revealed that densensitization of the pituitary actually occurred because pituitary concentrations of LH and FSH were suppressed, and additional treatment with GnRHa did not stimulate gonadotropin release from the already stimulated pituitary (Sudo et al 1990).…”
Section: Effects Of Gnrha On Corpora Lutea and Serum Progestins Lh Amentioning
confidence: 99%
“…Treatment with GnRH-a, especially long-term treatment, clearly reduced VEGF, VEGFR-1, and VEGFR-2 expression in the ovaries of hyperstimulated rats. We chose the amount of GnRH-a treatment to cause the desensitization of the pituitary in accordance with previously published reports (14,26).…”
Section: Kitajima Effect Of Gnrh-a On Hyperstimulated Rats Fertil Ste...mentioning
confidence: 99%
“…This discrepancy in the effects of the two dosage formulations on gonadotropin levels has also been observed in male rats [19]. Pituitary concentrations of LH and FSH are also lower in TAP-144-SR-treated than in TAP-144-solutiontreated male rats.…”
Section: Methodsmentioning
confidence: 63%
“…These results indicate that at the highest dose, the sustainedrelease formulation of TAP-144 is more effective than TAP-144 solution in suppressing ovarian hormone-dependent tissue growth. TAP-144-SR is also more effective than TAP-144 solution in suppressing testicular hormone-dependent accessory sex organ weight in male rats [19]. The reason why TAP-144-SR is more efficient than TAP-144 solution at the highest dose, and the reverse is true at the lowest dose may be explained as follows.…”
Section: Methodsmentioning
confidence: 96%